The Role of Cytoreductive Surgery and Hyperthermic Intraperitoneal Chemotherapy for Appendiceal Tumors and Colorectal Adenocarcinomas - Kuncewitch, Michael; Levine, Edward A.; Shen, Perry; Votanopoulos, Konstantinos I. (Clinics in Colon and Rectal Surgery, 2018)
Peritoneal surface disease (PSD) has historically been used interchangeably with the term peritoneal carcinomatosis (PC) and has a dismal natural history. A variety of malignant pathologies, including colorectal and appendiceal primary tumors, can disseminate throughout the peritoneal cavity, leading to bowel obstruction and death. In general, peritoneal spread from high-grade appendiceal and colorectal primaries has the potential of hepatic and distant spread and best classified as PC. Low-grade appendiceal tumors are better categorized as PSD, due to low cellularity, high mucin production, and lack of potential spread outside the peritoneal cavity. Growing international experience with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) over the past 30 years has presented a therapeutic option to patients with PSD from colorectal and appendiceal tumors that can provide significant disease control, as well as potential for previously unattainable long-term survival. The proliferation of HIPEC centers and ongoing prospective trials are helping to standardize HIPEC techniques and patient selection.
Keywords: peritoneal surface disease; peritoneal carcinomatosis; appendiceal cancer; hyperthermic intraperitoneal chemotherapy; colorectal adenocarcinoma; cytoreductive surgery; peritoneal metastasis